Education for Pregnant Women with Malocclusion in Their First, Second, and Third Trimesters Regarding the Risk of Gingivitis and Periodontitis: Edukasi Ibu Hamil dengan Maloklusi Pada Usia Produktif Trimester Satu Dua dan Tiga Terhadap Risiko Gingivitis dan Periodontitis - Muntadir, Lila; Rinata, Evi; Azhari, Tontowi; Puspitasari, Dini Ayu; Tsabita, Nabila Fatya (Universitas Muhammadiyah Sidoarjo, 2025)
Background: During pregnancy, physiological hormonal changes increase inflammatory responses, particularly in gingival tissue, making gingivitis and periodontitis more likely to occur, which can lead to pregnancy complications such as premature birth and low birth weight. This risk is even higher in pregnant women with malocclusion, especially during the first, second, and third trimesters. Therefore, appropriate and continuous education is crucial for pregnant women with malocclusion to enhance awareness of oral hygiene and health, as well as early detection during pregnancy. Objective: To implement preventive educational efforts targeting the risk of gingivitis and periodontitis among pregnant women with malocclusion who visit the Sedati Sidoarjo Health Centre, regardless of whether they are undergoing orthodontic treatment or not. Method: Interactive education and question-and-answer sessions based on extraoral and intraoral photographs and oral cavity examinations were conducted on 51 pregnant women who came for check-ups at the KIA clinic. All of the pregnant women had malocclusion, and 10 of them wore braces. The examination was conducted to assess the condition of the gums, teeth, and periodontal tissues. Results: The pregnant women enthusiastically participated in the activity, becoming familiar with the terms gingivitis, periodontitis, and malocclusion, and understanding the importance of maintaining oral hygiene, especially during pregnancy. The examination results showed that dental plaque (86.27%) and red gums (54.9%) were most prevalent among women aged 20–35 years and in the second and third trimesters. Conclusion: Interactive education combined with extraoral and intraoral examinations is highly effective in improving oral health during pregnancy and serves as an early detection method for gingivitis, periodontitis, and malocclusion. Most pregnant women with malocclusion in their reproductive years experienced gingivitis, and some also had periodontitis. Highlights: Hormonal changes increase gingivitis and periodontitis risk during pregnancy. Malocclusion worsens oral health issues, especially in the 2nd and 3rd trimesters. Interactive education and examinations improve awareness and early detection. Keywords: reproductive age of pregnant women, trimester of pregnancy, gingivitis, periodontitis in pregnant women, malocclusion in pregnant women